Development and Full Validation of a Monte Carlo Single-photon Emission Computed Tomography Camera Proposed for Coded Aperture Breast Tumor Imaging (Asian Journal of Pharmaceutics (AJP), 2025)
The Modified Uniformly Redundant Array (MURA) Coded Aperture (CA) imaging technique,initially developed for astronomical X-rays in far-field geometry, offers high Signal-to-Noise Ratio (SNR) andartifact-free imaging. Interest has grown in adapting MURA-CA to near-field geometry due to its high sensitivityand superior resolution, despite challenges related to artifacts. Materials & Methods: This study utilized MURAmasks, anti-masks, and subtraction techniques to exploit their delta correlation function. Simulations wereconducted with varying planar source sizes using 140 keV photons and Gaussian blurring to replicate real-worldconditions. Separate decoding functions were applied to reconstruct images from mask- and anti-mask-projecteddata. Metrics including resolution Full Width at Half Maximum (FWHM), contrast, SNR, root-mean-square error(RMSE), and correlation coefficients were evaluated. Results: MURA-CA exhibited significant SNR advantagescompared to pinholes and collimators. Near-field imaging, however, introduced artifacts that could be mitigatedby transitioning to far-field geometry, though at the expense of counting efficiency and SNR. Subtraction of maskand anti-mask images effectively minimized side lobe effects and reduced RMSE, achieving results comparable toindividual mask and anti-mask projections. Further enhancements were made by optimizing the trade-off betweenSNR and resolution under fixed time and dose conditions. Conclusion: MURA-CA is particularly well-suited forfar-field applications like breast tumor imaging, where artifacts are minimal. This study highlights the potential ofa MURA-CA system specifically designed for high-resolution SPECT imaging, integrated with a clinical gammacamera, to enable early tumor detection with improved imaging performance.